Dewaxing of Oil Pipelines by Applied Magnetic Field - Marzuki, Mohd Hakimi (IRC, 2018)

(untitled)
In production and transportation of raw petroleum, controlling the deposition of paraffin oil is the serious and expensive issues for crude oil which content high n- paraffin molecules. This holds particularly for offshore, deepwater wells and pipelines, like Malaysia. In discovering answers for these issues, a progression of analyses has been accomplish to investigate the impacts of magnetic field on the crude oil sample, utilizing the high and fluctuating magnetic field density of permanent magnet, Neodymium Iron Boron (Nd-Fe-B). The subsequent changes in the viscosity of the magnetically treated (MT) crude oil and their relationship between magnetic flux strength and temperature have demonstrated to utilize the NdFeB magnet as an ecologically friendly and effective strategy to control the deposition of paraffin. The effect of NdFeB on the wax deposition on the surface wall pipelines is also measured before and after applying magnetic treatment. By applying the magnetic field of 7890 Gauss, the viscosity of Tapis crude oil can decrease up to 40.23% while the reduction of wax deposited on wall pipelines was 33.33%. Based on these data obtained from the study, it can serve as a fundamental in planning and development of the NdFeB permanent magnet as an effective tool to enhance the flow of high paraffin content in crude oil.